2021
DOI: 10.17221/167/2020-swr
|View full text |Cite
|
Sign up to set email alerts
|

Thallium uptake/tolerance in a model (hyper)accumulating plant: Effect of extreme contaminant loads

Abstract: Thallium (Tl) is a toxic trace element with a highly negative effect on the environment. For phytoextraction purposes, it is important to know the limitations of plant growth. In this study, we conducted experiments with a model Tl-hyperaccumulating plant (Sinapis alba L., white mustard) to better understand the plant tolerance and/or associated detoxification mechanisms under extreme Tl doses (accumulative 0.7/1.4 mg Tl, in total). Both the hydroponic/semi-hydroponic (artificial soil) cultivation variants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This study has shown that S. latifolia accumulates Tl in response to increasing Tl concentrations in a hydroponic system. In a similar Tl dosing trial with Sinapis alba exposed to 2 mg Tl L −1 , the highest Tl in shoots was 87.2 μg g −1 (Holubík et al 2021), whereas in our experiment at 5 μM Tl (corresponding to 1 mg Tl L −1 ) S. latifolia attains 705 ± 466 μg Tl g −1 in young leaves, and even more Tl is taken up in the higher Tl treatments, thereby showing that it is demonstrably highly Tl tolerant.…”
Section: Discussionmentioning
confidence: 95%
“…This study has shown that S. latifolia accumulates Tl in response to increasing Tl concentrations in a hydroponic system. In a similar Tl dosing trial with Sinapis alba exposed to 2 mg Tl L −1 , the highest Tl in shoots was 87.2 μg g −1 (Holubík et al 2021), whereas in our experiment at 5 μM Tl (corresponding to 1 mg Tl L −1 ) S. latifolia attains 705 ± 466 μg Tl g −1 in young leaves, and even more Tl is taken up in the higher Tl treatments, thereby showing that it is demonstrably highly Tl tolerant.…”
Section: Discussionmentioning
confidence: 95%
“…Chang et al [ 45 ] also describe the antagonistic effect of Tl and K in Arabidopsis, in which Tl interferes with the K uptake. In Sinapis alba that are grown in hydroponic culture, the effect of Tl is to reduce the K content in the roots, as well as in the stems and leaves [ 50 ]. With regard to Mg, the Tl inhibits its absorption in Dittrichia , decreasing the content in the roots.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the increase in TF Mg and the lower effect that is observed on the Mg content in the leaves, this does not prevent the decrease in the chlorophyll content. In contrast, in S. alba , Holubick et al [ 50 ] describe low Tl concentrations leading to a decrease in Mg in shoots but not in roots, whereas, in C. annuum, the changes in the Mg content depend on the variety [ 88 ]. With regard to the Ca content, the data show that there is a decrease in its accumulation in the roots, except for those with the highest concentration that was used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations